Abacavir/lamivudine combination in the treatment of HIV: a review - Geetha Sivasubramanian; Emmanuel Frempong-Manso; Rodger D MacArthur (Dove Medical Press, 2010)
Geetha Sivasubramanian1, Emmanuel Frempong-Manso2, Rodger D MacArthur11Division of Infectious Diseases, Wayne State University, Detroit, MI, USA; 2University of Pittsburgh Medical Center, Shadyside Hospital, Pittsburgh, OH, USAAbstract: Abacavir has been at the center of research and clinical interest in the last two years. The frequency of the associated abacavir hypersensitivity syndrome has decreased substantially since the introduction of routine testing for the HLA-B*5701 allele; the activity of the drug in HIV-infected persons with HIV RNA values more than 100,000 copies/mL has been questioned; the possible increased risk of myocardial infarction after recent exposure to abacavir has been debated; and the drug has been moved from the “recommended” category to the “alternative” category in several guidelines. Still, the drug remains a useful agent in combination with other drugs, including lamivudine, for the treatment of HIV infection. This review will focus on the pharmacokinetics, activity, side effects, and resistance profile of both abacavir and lamivudine, including a thorough review of all of the recent studies relevant to both drugs.Keywords: HIV, abacavir, lamivudine